Minutes of General Council (extract)
017a-0036-001 G.C. -1 SEP. 1938 283. UNION GENERAL DE TRABAJADORES DE ESPANA, BARCELONA. Message was received from the Union General de Trabajadores de Espana, Barcelona, conveying their best wishes for the success of the deliberations at Congress on behalf of the workers and signifying their gratitude for the solidarity which the British workers were showing towards them in their war, and which they hoped might still further be intensified from now on in proportion to the necessities of their struggle to drive the invaders from Spanish soil. NOTED and AGREED it should be read to Congress. 292/946/17a/36